The dust-continuum size of TNG50 galaxies at z = 1-5: a comparison with the distribution of stellar light, stars, dust, and H2 - Popping, Gergö; Pillepich, Annalisa; Calistro Rivera, Gabriela; Schulz, Sebastian; Hernquist, Lars; Kaasinen, Melanie; Marinacci, Federico; Nelson, Dylan; Vogelsberger, Mark (Monthly notices of the Royal Astronomical Society, 2022)
We present predictions for the extent of the dust-continuum emission of main-sequence galaxies drawn from the TNG50 simulation in the range z = 1-5. We couple the radiative transfer code SKIRT to the output of the TNG50 simulation and measure the dust-continuum half-light radius of the modelled galaxies, assuming a Milky Way dust type and a metallicity-dependent dust-to-metal ratio. The dust-continuum half-light radius at observed-frame 850 $\m